Characterization of Multiple-bend Optical Fiber Extensometer Design for Landslide Sensor - Costrada, Aldo Novaznursyah; Deswilan, Sixtinah; Kemal, Badrul Mustafa; Harmadi, Harmadi (Universitas Andalas, 2021)
Design of multiple-bend extensometer based on optical fiber as landslide sensor has been characterized. Multiple-bending characterization has been done by varying the winding number of optical fiber FD-620-10 to obtain the photodiode's effective light intensity.Â The light intensity in the extensometer was set by varying the laser diode resistance in the range (150 â€“ 250) Î©.Â The optimum sensitivity of 0.03984 V/cm was obtained for triple winding of optical fiber. The designed optical extensometer is able to monitor the displacement with an error of 0.59%. This result indicates that the designed extensometer is the more bending on optical fiber, the more its sensitivity and the bending loss.